Pengobataan Tibbun Nabawi Perspekif Al Islam Kemuhammadiyaan Dan Medis - Rizlah Maulizah; Oman Fathurohman SW (STIKes Ibnu Sina Ajibarang, 2024)
Abstract. Thibbun Nabawi's medicine, which originates from Islamic teachings and was taught by the Prophet Muhammad SAW, has become an interesting subject of study in the health context. In the Al-Islam perspective, this treatment is seen as an integral part of worship and plays an important role in maintaining the physical and spiritual health of Muslims. This aim is to strengthen understanding of the relevance and application of Tibbun Nabawi in the modern context, especially among the Muhammadiyah community and in the medical world. This research uses qualitative methods with the type of library research. Literature research involves collecting and analyzing data from various relevant literature, including books, scientific journals, articles, and other documents that discuss Tibbun Nabawi, Muhammadiyah perspectives, and medical views. This article presents the results of research and discussions about the integration of Tibbun Nabawi with modern medicine, taking into account Al-Islam, Muhammadiyah and medical perspectives. By combining traditional knowledge and modern medical science, Thibbun Nabawi has the potential to become an important part of a holistic and effective health system for society.